Abraham's Faith in Kierkegaard's Conception: An Analysis of the “Fear and Trembling” Book - Mihai Handaric (Randwick International of Social Science Journal, 2021)
The author of the article "Abraham's faith in Kierkegaard's conception: an analysis of the books 'Fear and Trembling,'" analyzes the theme of faith from the perspective of the Danish philosopher Søren Kierkegaard. The philosopher was impressed by the adventure of the faith of Abraham who was challenged to sacrifice his son at the command of Yahweh (Gen. 22). The paper tries to find the explanations of philosophy, with reference to the acceptance of the divine challenge, by Abraham, who seems inhuman and irrational. We will analyze the expression used by Kierkagaard, who calls Abraham the "Knight of the Faith," in what sense, paradoxically, by faith did Abraham win Isaac? What is the significance of the knight of resignation, with reference to the one who refuses the act of faith, and wants to keep the temporality. We will see that from his point of view, the believer cannot accept advice, he will travel alone on this path. The logic of faith, the silence and the fear of faith are analyzed. The relationship between ethics and faith is also discussed. We will discuss the ethics that Kiergegaard refers to, as a set of moral rules shared by a human community - the moral consensus shared by a majority, which seems to be at odds with biblical faith. It also assesses the benefits of faith, in contrast to living by sight, and why Abraham became a guiding star.